Orbital infarction syndrome following hyaluronic acid filler rhinoplasty - Eldweik, Luai (Am J Ophthalmol Case Rep, 2021)
PURPOSE: Over the last decade, injectable soft tissue fillers have become an essential part of facial plastic surgery practice. We report here a tragic complication of hyaluronic acid filler injection in a young healthy woman, management offered, and the outcome. OBSERVATIONS: A 32-year-old woman developed unilateral acute blindness, orbital pain, total ophthalmoplegia, and anterior and posterior segment ischemia immediately following hyaluronic acid injection. Urgent measures were taken including hyaluronidase enzyme injection, vigorous messaging, and systemic steroids. Eight weeks later, the extraocular motility has fully recovered; however, the consequences of ischemia on the anterior and posterior ocular segments persisted. CONCLUSIONS AND IMPORTANCE: Describing a major refractory complication following injecting hyaluronic acid dermal filler. Prompt intervention including the use retro or peribulbar injection of hyaluronidase has a little impact when it comes to reversing ocular sequalae. Therefore, injectors should be aware of facial danger zones that could potentially lead to this devastating outcome.